Factors of Consumers Purchase Intention at Halal Restaurants - Lestari, Dwi Putri; Wahyono, Wahyono (Universitas Negeri Semarang, 2022)
The purpose of this study was to determine the factors of consumer purchase intention at a halal restaurant with halal awareness as a moderation (a case study on consumers of Waroeng Steak & Shake Semarang). The population in this study are consumers who have purchased products at Waroeng Steak & Shake Semarang. The number of samples used in the study were 115 people, using the method non-probability sampling. Methods of data collection using a questionnaire method. The results of data analysis using the SPSS version 21 program show that there is a positive and significant effect of halal label and Islamic branding on purchase intention. And the halal awareness variable becomes a moderator between the Islamic branding variable on purchase intention, as well as a moderating predictor on the relationship between halal labels and purchase intentions.